Association of body mass index changes with short-term mortality risks in ICU patients with sepsis across different admission BMI states: analysis of the MIMIC-IV database - Liu, Wei; Zeng, Wenfei; Huang, Zhenhua; Yuan, Qinghua (Frontiers in Immunology, 2025)
BackgroundStatic body mass index (BMI) is a known predictor of mortality in sepsis; however, the prognostic value of dynamic BMI trajectories across various admission BMI states remains unclear. This study aimed to quantify the dose–response relationship between ICU-acquired BMI changes and 30-day mortality and to determine BMI-specific thresholds for risk stratification.MethodsThis retrospective, multicenter cohort study analyzed 5,577 adult patients with sepsis from the MIMIC-IV database (2008–2022). To delineate the nature of the relationship between BMI change rate and 30-day mortality across distinct baseline BMI strata, we employed multivariable Cox proportional hazards regression coupled with restricted cubic splines. A two-segment linear regression model with a recursive algorithm was then applied to pinpoint inflection points for each BMI-defined subgroup.ResultsAmong 5,577 ICU patients with sepsis (mean age 66.5 ± 15.8 years; 57.4% male), 2,068 deaths (37.1%) occurred within 30 days. BMI change during the ICU stay ranged from −39% to +49%. After multivariable adjustment, each 1% increase in BMI change rate was associated with a 2% higher 30-day mortality (hazard ratio [HR] 1.02; 95% confidence interval [CI] 1.02–1.02; p < 0.001). However, in the underweight subgroup (<18.5 kg/m²), no significant association was observed (HR 0.99; 95% CI 0.98–1.00; p = 0.093). Restricted cubic spline analyses revealed BMI-specific inflection points: −2% in underweight, +4% in normal-weight (18.5–24.9 kg/m²), and −1% in overweight/obese (≥25 kg/m²) patients (p for nonlinearity < 0.001 for all). Dynamic BMI metrics significantly outperformed admission BMI in predicting 30-day mortality (p < 0.001).ConclusionIn critically ill ICU patients with sepsis, the relationship between BMI change (%) and 30-day mortality is nonlinear and varies across baseline BMI. Among patients with an admission BMI ≥18.5 kg/m², an increase in BMI during the ICU stay is associated with higher mortality risk, indicating that weight gain is deleterious. Conversely, in patients with an admission BMI <18.5 kg/m², a decline in BMI markedly amplifies the risk of death. Tailored and dynamic weight management strategies accounting for baseline BMI trajectories may therefore help mitigate sepsis-related mortality.